Population genetics of Lepidoglyphus destructor inferred by the analysis of the mitochondrial cytochrome b gene and ribosomal internal transcribed spacer gene sequence. Issue 8 (17th November 2021) - Li, Xinmei; Tao, Xianglin; Wang, Yan; Ma, Fei; Ye, Changjiang; Zhou, Xiaoqian; Tao, Jichun; Liu, Fei; Sun, Entao
ABSTRACT: The storage mite, Lepidoglyphus destructor, occurs in both rural and urban environments worldwide. It poses an allergenic threat to humans and damages stored grain. Most studies on L. destructor have focused on its allergens, but much less is known about its genetic diversity and genetic structure. This information would be helpful for comprehensive control of this species and other indoor allergenic mites. The genetic diversity and structure of four L. destructor populations were studied using the mitochondrial cytochrome b ( Cytb ) region and the ribosomal internal transcribed spacer ( ITS ) region. We obtained 30 Cytb gene sequences and 38 ITS gene sequences from four localities in China and 17 and 33 haplotypes, respectively. The length of Cytb sequences was 372 bp, and the length of ITS sequences varied from 1301 to 1320 bp. DnaSP 5.10 analysis showed that both Cytb and ITS sequences of L. destructor in the four populations had high genetic diversity. These data suggest that L. destructor has high environmental adaptability. Analysis of molecular variance (AMOVA) based on Cytb showed that the variation was mainly among populations (92.28%) with significant genetic structure, whereas the variation based on ITS was mainly within the populations (69.86%) without a significant genetic structure. Maximum likelihood (ML) tree and haplotype network diagrams based on Cytb and ITS consistently showed that the four populations of L. destructor could be divided into two clades: clade A (WH, HZ and HF) and clade B (CQ). The genetic differentiation index ( FST ) showed that the CQ population was significantly differentiated from the other three populations ( FST > 0.25). The long geographical separation distance and low frequency of trade activities may help explain the high level of genetic differentiation in the CQ population, while the low level of genetic differentiation among WH, HF, and HZ populations may reflect the high level of gene flow. This study improves our understanding of the population genetics of L. destructor, which would be useful for developing effective management strategies and future research of L. destructor in directions.